Prevention and Reduction of Obesity through Active Living (PROACTIVE): rationale, design and methods. Issue 1 (10th November 2008) - Ross, R; Blair, S N; Godwin, M; Hotz, S; Katzmarzyk, P T; Lam, M; Lévesque, L; MacDonald, S
Abstract : The Prevention and Reduction of Obesity through Active Living (PROACTIVE) is a randomised controlled trial to evaluate the effectiveness of a behaviourally based physical activity and diet composition programme to prevent and reduce obesity and related comorbidities in a primary healthcare setting. 491 abdominally obese men and women 25–75 years of age who were patients of primary care physicians were randomly assigned to either a usual care group (N  =  242) or a behavioural intervention group (N  =  249). Those in usual care received general advice from the physician regarding the merits of physical activity and a healthy diet as a strategy for obesity reduction. Those in the behavioural intervention group received an individually designed counselling programme from a specially trained health educator, with respect to physical activity, diet and obesity reduction. The study was designed to provide 95% power in both men and women to detect a 2% (2 cm) difference in waist circumference and 80% power to identify a 15% reduction in the prevalence of the metabolic syndrome, the two primary outcomes. PROACTIVE is the first behavioural intervention study to assess the effects of physical activity and diet on abdominal obesity and associated metabolic risk factors in a primary healthcare setting, include a generalised sample of men and women and examine long-term (24 months) effects. PROACTIVE has the potential to provide the basis for changing clinical practice (primary care) with respect to the prevention and reduction of obesity and related health risks. The purpose of this report is to present and discuss the rationale, design and methods of PROACTIVE.